Adult attachment is related to maternal neural response to infant cues: an ERP study. Issue 1 (2nd January 2023) - Lowell, Amanda F.; Dell, Jaclyn; Potenza, Marc N.; Strathearn, Lane; Mayes, Linda C.; Rutherford, Helena J. V.
ABSTRACT: Maternal attachment security is an important predictor of caregiving . However, little is known regarding the neurobiological mechanisms by which attachment influences processing of infant cues, a critical component of caregiving. We examined whether attachment security, measured by the Adult Attachment Interview, might relate to neural responses to infant cues using event-related potentials. Secure ( n =35) and insecure ( n =24) mothers viewed photographs of infant faces and heard recordings of infant vocalizations while electroencephalography was recorded. We examined initial processing of infant faces (N170) and cries (N100), and attentional allocation to infant faces and cries (P300). Secure mothers were significantly faster than insecure mothers to orient to infant cries (N100), structurally encode their own infant's face (N170), and attend to infant faces (P300). These differences may elucidate mechanisms underlying how attachment may shape neural processing of infant cues and highlight the use ofsocial neuroscientific approaches in examining clinically relevant aspects of attachment.